Impact of packaging revolution on China's dairy product industry - Wan, Jiyang (2008)
Review the development of the dairy industry as well as the milk consumption market, analyze the driving forces behind the changes, highlighting how innovations in packaging brings new opportunities and challenges to the milk manufacturers and propose a framework for milk manufacturers to make strategic development decisions.